CSR Strategies in Response to Competitive Pressures - Dupire, Marion (Journal of business ethics, 2018)
Is corporate social responsibility (CSR) a tool for strategic positioning? While CSR is sometimes used as part of a differentiation strategy, this article analyzes which specific CSR strategies arise in response to competitive pressures. The results suggest that competitive pressures lead firms to increase their positive social actions without necessarily decreasing their social weaknesses. This positive impact varies with specific dimensions of CSR and industry specificities: (1) Competition improves social performance toward core stakeholders to a greater extent than social performance toward peripheral stakeholders. (2) This effect is more pronounced in B2C industries than in other industries. (3) Competition leads firms in “dirty” industries to ignore environmental initiatives.